Understanding Acute Coronary Syndrome (IntechOpen, 2026)
Understanding Acute Coronary Syndrome - Symptoms, Causes, and Treatment Options offers a comprehensive and practical guide to one of the most urgent conditions in modern medicine. From unstable angina to myocardial infarction, this textbook explores ACS in depth, examining its complex causes, diverse presentations, and evolving treatment strategies. Tailored for healthcare professionals at all levels, the book bridges cutting-edge science with real-world clinical care. It covers special populations, advanced diagnostic tools like cardiac MRI, arrhythmic complications, protocol-driven management, and even complementary therapies such as Traditional Chinese Medicine. Rich with insight and grounded in evidence-based practice, this resource equips clinicians with the knowledge needed to deliver patient-centered, high-quality care in the face of a life-threatening challenge.